A proposed model of factors influencing hydrogen fuel cell vehicle acceptance - Imanina N.H.N.; Lu T.K.; Fadhilah A.R. (Institute of Physics Publishing, 2023)
Automotive industry; Energy utilization; Fuel cells; Hydrogen fuels; Risk perception; Environmental problems; Government intervention; Hydrogen fuel cell vehicles; Perceived behavioural controls; Technology acceptance; Theory of planned behaviour; Vehicle acceptance; Zero emission vehicles; Vehicles; advanced technology; alternative energy; conceptual framework; empirical analysis; energy planning; energy use; environmental modeling; environmental technology; fuel cell; hydrogen; perception; public attitude; technology adoption; transport vehicle